Energy optimal control of an over-actuated hybrid feed drive under variable-frequency disturbances —​ with application to machining. (July 2020) - Duan, Molong; Ramani, Keval S.; Okwudire, Chinedum E.
Abstract: Machine tool feed drives are often subject to variable-frequency disturbance (cutting) forces due to varying spindle speeds or cutting tools. A proxy-based control allocation method has been proposed for energy optimal control of over-actuated systems (i.e., systems with more actuators than the number of outputs to be controlled). It has been applied to an over-actuated hybrid feed drive, consisting of a linear motor drive coupled to a screw drive, and its effectiveness has been demonstrated under fixed-frequency disturbance forces. This paper discusses the fundamental limit of the fixed-frequency approach and extends the proxy-based control allocation method to account for variable-frequency disturbance forces via a linear parameter-varying formulation. The controller gains are optimized using linear matrix inequality and scheduled as a function of disturbance frequency. Significant improvements in energy efficiency are demonstrated in simulations and experiments using the proposed gain-scheduling approach compared to the existing fixed-frequency approach.